Os limites da democracia liberal: o influxo do poder econômico no exercício das liberdades - Barbosa, Gustavo Henrique Freire (2017)
The research deals with the limits of liberal democracy in its traditional and contemporary dimensions, developing how the predominantly formal conception of the exercise of constitutional freedoms, rights and guarantees affects the programmatic objectives born from the emergence of a constitutional order where democracy is expressed in institutes that are far beyond suffrage, underutilized for not matching the objectives embodied in the material conditions of production in which the relations involving the State are located as a promoter of rights and a driver of public policies. The work also addresses the lack of normativity and social effectiveness of normative provisions, showing the paradoxical effects of a constitutional order situated under the contours of the capitalist mode of production, as well as the contradictions which exists between the legal prediction of rights and the rationality of a society immersed in the dynamics of an ever greater transnationalization of the economy, identifying the material incompatibilities of the realization of rights already institutionalized with the values from the market economy in its postmodern expression.